MODELLING AND ANALYSIS ON WATER PRODUCTIVITY IN TANK IRRIGATED SYSTEM USING HYDROLOGICAL MODEL - B, Sangeethavani (International Journal of Psychosocial Rehabilitation, 2012)
As a limited and essential natural resource, water has played a significant role in the advancement of human civilisation. Agricultural production systems need it as a critical input to produce both food and fibre. By 2025, the world's population will have surpassed the two billion mark, and the domestic food grain consumption is expected to be between 241 and 245 million tonne. The amount of water that can be withdrawn from river basins to supply the rising demand for food is limited, as the maximum withdrawal has already been reached. Irrigated agriculture will be affected by the need to supply water for the home, industrial and environmental needs. In order to continue producing food for the future, more water must be drained from natural resources. Agricultural output must therefore focus on increasing water efficiency.